A new approach to chronotype measurement - the Polish version of the Single Item Chronotyping (SIC) tool. Issue 3 (4th March 2023) - Nowakowska-Domagała, Katarzyna; Juraś-Darowny, Małgorzata; Pietras, Tadeusz; Sipowicz, Kasper; Stecz, Patryk; Mokros, Łukasz
ABSTRACT: The aim of the study is to validate the Polish version of the Single Item Chronotyping (SIC) tool, and thus confirm the relevance of Putilov's six chronotypes. The SIC was used as an instrument intended to identify patterns of changes in alertness occurring throughout the day. The external validity of the SIC was confirmed by comparison to the Composite Scale of Morningness (CSM) scores, midsleep time on working days, midsleep time on free days and social jetlag. The sample consisted of 436 adult participants, with a mean age of 24.98 ± 8.41 (range 18 to 63). In a study sample, each SIC type was represented by at least 10% of participants. Differences were noted between SIC groups in a Composite Scale of Morningness. The relevance of Putlov's chronotypology was confirmed for the Polish population. It may be possible to effectively measure chronotype with this single-item tool.